How social background and interest in science are linked to junior high school students’ perceptions of the ecological transition - Nadarajah, Kévin; Somat, Alain; Baeyens, Céline; Pansu, Pascal (Frontiers in Psychology, 2024)
Junior high school students are tomorrow's key protagonists in the ecological transition. They need enlightened education to face the uncertainty and challenges of climate change. The development of climate change education programs requires a clear understanding of how young people perceive the issue. This study deals with social representations. Its aim was to understand how social background and interest in science are linked to the way young people perceive the concept of the ecological transition. 429 junior high school students took part in this study. Data were collected and subjected to prototypical analysis and factorial correspondence analysis. Three main findings emerged from the analysis: (1) the participants had significant knowledge of the ecological transition, (2) their awareness of the social aspects of climate change was limited, and (3) their representations of the ecological transition were linked to their interest in science and their parents' social background. To conclude, these results underline the importance of educating all social classes about effective solutions for the ecological transition. Our findings also highlight the need to consider existing representations and prior knowledge when designing educational programs on climate change issues.